Rapid human population growth and its impacts on danau sentarum - Indriatmoko, Y. (2010)
In the past decade, Indonesia's protected areas have been threatened not only by illegal logging and mining, poaching, and other illegal activities, but also by the increasing population of the local communities. Many of these local communities depend on the natural resources of the protected areas. This paper presents the case of Danau Sentarum National Park (DSNP), where the human population inside the park has grown rapidly, and discusses the implications for the conservation area.